2020
DOI: 10.37201/req/037.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic syndrome in patients infected with the human immunodeficiency virus: A study of 15 consecutive patients

Abstract: Objectives. Hemophagocytic syndrome (HPS) is characterized by various clinical and biological data derived from cytokine hyperproduction and cell proliferation. The objectives of this study were to evaluate the epidemiological, etiological, clinical and evolutionary characteristics of patients diagnosed with hemophagocytic syndrome and HIV infection, as well as their comparison with data from the literature. Methods. A retrospective descriptive observational study was performed, including all adult patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(100 reference statements)
0
3
0
Order By: Relevance
“… 7 - 10 The most frequent malignancies associated with HLH are lymphoma, and related autoimmune diseases such as systemic lupus erythematosus and adults Still’s disease. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 7 - 10 The most frequent malignancies associated with HLH are lymphoma, and related autoimmune diseases such as systemic lupus erythematosus and adults Still’s disease. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Four other studies tried to evaluate the association between HIV and HLH [24][25][26][27]. A large study with 3066 patients with HIV noticed that the most common symptoms in immunocompromised patients with HLH were fever, cytopenias, and elevated ferritin.…”
Section: Hlh and Infectionsmentioning
confidence: 99%
“…A large study with 3066 patients with HIV noticed that the most common symptoms in immunocompromised patients with HLH were fever, cytopenias, and elevated ferritin. In contrast, 33% of the patients presented CNS involvement [ 24 ]. In addition, another study by Lerolle et al suggested that in immunocompromised patients, HIV was considered a predisposing condition for hemophagocytic syndrome and was not the actual trigger for HLH [ 25 ].…”
Section: Reviewmentioning
confidence: 99%